Life cycle assessment of microbial 2,3-butanediol production from brewer’s spent grain modeled on pinch technology - Tiwari, Bikash R.; Bhar, Rajarshi; Dubey, Brajesh K.; Maity, Sunil K.; Brar, Satinder Kaur; Kumar, Gopalakrishnan; Kumar, Vinod (American Chemical Society, 2023)
Microbial production of 2,3-butanediol (BDO) has received considerable attention as a promising alternate to fossil-derived BDO. In our previous work, BDO concentration >100 g/L was accumulated using brewer’s spent grain (BSG) via microbial routes which was followed by techno-economic analysis of the bioprocess. In the present work, a life cycle assessment (LCA) was conducted for BDO production from the fermentation of BSG to identify the associated environmental impacts. The LCA was based on an industrial-scale biorefinery processing of 100 metric tons BSG per day modeled using ASPEN plus integrated with pinch technology, a tool for achieving maximum thermal efficiency and heat recovery from the process. For the cradle-to-gate LCA, the functional unit of 1 kg of BDO production was selected. One-hundred-year global warming potential of 7.25 kg CO2/kg BDO was estimated while including biogenic carbon emission. The pretreatment stage followed by the cultivation and fermentation contributed to the maximum adverse impacts. Sensitivity analysis revealed that a reduction in electricity consumption and transportation and an increase in BDO yield could reduce the adverse impacts associated with microbial BDO production.
Keywords: 2,3-Butanediol; brewer’s spent grain; global warming; life cycle assessment; sensitivity analysis; biorefinery